ANALISIS KEMISKINAN NELAYAN PERIKANAN TANGKAP DI PANTAI SENDANG BIRU KABUPATEN MALANG, JAWA TIMUR - Ariyanti, Yusfi Ikrima (Jurnal Ilmiah Mahasiswa FEB, 2016)
When we talk about poverty, it becomes complicated and up until now to the present reducing to reduce the level of poverty is very difficult. Especially with Indonesia which is a maritime country, but the level of poverty in coastal areas is still fairly high. It has also been experienced by fishermen at Sendang Biru Beach Malang that have a high potential for fisheries. Thus study aims to analyze why poverty rate is still quite high in the area of ​​marine potentials. This paper views poverty from two perspectives: the perspective of economic and non-economic. There are two groups of fishermen in Sendang Biru Beach: local fishermen and entrants fisherman. The research shows that entrants fisherman has more excellence in terms of technology, capital ownership, organization managing and social capital compared to local fishermen. But, both of them has an equal chance in terms of market acces. So, local fishermen have difficulties to develop, especially with consumption and distribution pattern which complicates local fishermen. Keyword: poverty, fisherman,